Effect of nitrogen sources on gene expression of Stevia rebaudiana (Bertoni) under in vitro conditions - Akbari, Fariba; Arminian, Ali; Kahrizi, Danial; Fazeli, Arash; Ghaheri, Matin (Cellular and Molecular Biology, 2018)
Stevia rebaudiana (Bertoni) is a non-caloric sweetener belonging to Asteraceae family. Stevia compounds such as steviol glycosides (SGs) are 200 times sweeter than sugar. Stevioside and rebaudioside A are the two major steviol glycosides. Nitrogen is an essential element for plant growth and development. In this study the effects of nitrogen influenced by different concentrations of NH4NO3 (0, 825 and 1650 mg/l) and KNO3 (0, 950 and 1900 mg/l) is examined in MS medium. To analysis the UGT74G1 and UGT76G1 genes expression, involved in the synthesis of SGs, RT-qPCR technique was performed. Data showed that there were significant differences between all media. The shoot length, seedlings dry weight and leaf fresh weight of stevia increased with applying NH4NO3 along with KNO3. The highest expression of UGT74G1 gene, was observed in plantlets grown on MS medium with 0 mg/l NH4NO3 and 950 mg/l KNO3 (1.291 total lab unit) but the highest expression of UGT76G1 gene, was observed in plantlets grown on MS medium added by 1650 mg/l NH4NO3 +950 mg/l KNO3 (1.08 total lab unit). Moreover, the lowest value of UGT74G1 gene expression were revealed in MS medium added by 1650 mg/l NH4NO3 +0 mg/l KNO3 (0.80 total lab unit) and the lowest values of UGT76G1 gene expression seen in MS medium with 0 mg/l NH4NO3 +950 mg/l KNO3 (0.85 total lab unit) concentrations. The results of this study could be valuable in stevia breeding programs through glycosides biosynthesis pathways.